CHARACTERISTICS MICROPLASTICS AND ESTIMATED DAILY INTAKE (EDI) IN KUPANG PUTIH (Corbula faba Hinds.) AND KUPANG MERAH (Musculista senhousia) - Abrila Delita Putri Siswanto; Aunurohim Aunurohim; Dian Saptarini (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2025)
Microplastics are plastic polymer particles smaller than 5 mm that can enter aquatic organisms through ingestion or trophic transfer. Bivalves are particularly vulnerable to microplastic contamination due to their filter-feeding behavior, which may pose potential risks not only to aquatic ecosystems but also to human health through seafood consumption. However, information on microplastic characteristics and human exposure assessment in locally consumed bivalves from the Madura Strait remains limited. This study aimed to analyze the physical and chemical characteristics of microplastics and to estimate human exposure using the Estimated Daily Intake (EDI) approach in two edible bivalve species, namely white mussel (Corbula faba Hinds.) and red mussel (Musculista senhousia), collected from the Madura Strait, Indonesia. A total of 30 individuals per species were analyzed. Physical characteristics of microplastics, including shape, size, and color, were observed using a stereomicroscope, while polymer types were identified using ATR–FTIR analysis. The EDI method was applied to estimate the potential daily intake of microplastics by humans through mussel consumption. The average microplastic abundance was higher in C. faba (104.6 ± 33.23 particles/individual) than in M. senhousia (53.46 ± 18.91 particles/individual). Fragment-shaped, black-colored microplastics with sizes of 10–50 µm were dominant in both species. Polypropylene (PP) and nylon or polyamide (PA) was the main polymer types identified. The estimated daily intake of microplastics was 1,067.24 particles/person/day for C. faba and 335.55 particles/person/day for M. senhousia. This study provides new insights by integrating microplastic characterization with human exposure assessment using EDI, highlighting the potential risks associated with bivalve consumption and supporting future environmental monitoring and food safety management.